Thinking (with) the Unconscious in Media and Communication Studies: Introduction to the Special Issue - Krüger, Steffen; Johanssen, Jacob (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
Under the title Digital Media, Psychoanalysis and the Subject, this special issue of CM: Communication and Media seeks to reassess and reinvigorate psychoanalytic thinking in media and communication studies. We undertake this reassessment with a particular focus on the question of what psychoanalytic concepts, theories as well as modes of inquiry can contribute to the study of digital media. Overlooking the field of media and communication studies, we argue that psychoanalysis offers a reservoir of conceptual and methodological tools that has not been sufficiently tapped. In particular, psychoanalytic perspectives offer a heightened concern and sensibility for the unconscious, i.e. the element in human relating and relatedness that criss-crosses and mars our best laid plans and reasonable predictions. This introduction provides an insight into psychoanalysis as a discipline, indicates the ways in which it has been adopted in media research in general and research into digital media in particular and, ultimately, points to its future potential to contribute to the field.